Policy agenda toward a hydrogen economy: Institutional and technological perspectives - Lee, Youhyun; Cho, Min Hyuk; Lee, Min Chul; Kim, Young Jin (International Journal of Hydrogen Energy, 2024)
The South Korean government aims to become a global leader in the hydrogen economy. However, policymakers and experts remain concerned about the gap between the institutional and technological perspectives. Based on socio-technical system theory, the transition to a hydrogen economy can be achieved through the co-evolution of both technology and institutions. Through expert surveys, this study explores core keywords and clusters using semantic network analysis. Consequently, four and six clusters are identified as vulnerable from technological and institutional perspectives, respectively. Overall, hydrogen-related institutions must develop and support the fast-growing hydrogen technologies. The South Korean case offers practical policy implications for the co-evolution of the socio-technical system toward a transition to a hydrogen economy.
Keywords: Co-evolution; Expert survey; Hydrogen economy; Hydrogen policy agenda; Institutional perspective; Korean Government; Policy makers; Semantics networks; Sociotechnical systems theory; Technological perspective; Expert survey; Hydrogen economy; Hydrogen policy agenda; Semantic network